A Non-Experimental study to assess the knowledge and opinion regarding written consent in hospital practice among patients and family members in selected health care institute of Pune city. - Mr.Abhijeet Mahale, Mrs.Archala Khemnar (Drugs and Cell Therapies in Hematology, 2021)
Informed consent for clinical treatment has become a vital part of contemporary medical practice; it means different things in different contexts, is variably practiced and rarely achieves the theoretical ideal. Informed consent has become the primary paradigm for protecting the legal rights of patients and guiding the ethical practice of medicine. It may be used for different purposes in different contexts: legal, ethical or administrative. Study title: “Knowledge and opinion regarding written consent in hospital practice among patients and family members.” Materials and Methods: The study adopted Non-Experimental Descriptive design carried out among 200 subjects (100 patients and 100 family members). Non-probability purposive sampling technique was used and was statically analysed after collecting the data through A structured questionnaire for assessing the knowledge and opinion regarding written consent. Ethical clearance was taken from the Institutional ethics committee. Data analysis was done using descriptive statistics. Results: The study results showed that majority 61% of patients have average knowledge, 23% samples have good knowledge and 16% samples have poor knowledge with the mean of 9.36 and SD of 3.39. The majority of samples 66% in group of family members have average knowledge, 25% samples have good knowledge and 11% samples have poor knowledge with the mean of 9.95 and SD of 3.20. Conclusion: The findings of the study showed demographic variables like age and marital status of the patients are associated with the knowledge regarding written consent while only marital status of the family members is associated with the knowledge regarding written consent. Opinion wise distribution shows that family members and patients are having similar opinion regarding written consent in hospital practice. Recommendation: It is suggested that a similar study can be indicated with a larger population.